Engineering of Soil Biological Quality from Nickel Mining Stockpile Using Two Earthworm Ecological Groups - Kilowasid, L M H; Herlina, H; Syaf, H; Safuan, L; Tufaila, M; Leomo, S; Widiawan, B (Brawijaya University, 2015)
Earthworms have the ability in modifying soil biological quality for plant growth. Their ability is mostly depending on its ecological groups. The objectives of the research were to study the influence of two ecological groups of earthworms on soil microbial activity and soil micro-fauna abundance, and to know the potential of soil modified by earthworms as plant growth medium. Eight combination of individual earthworm from epigeic and endogeic groups was applied into pot Â that was filled by soil from two years ofÂ nickel stockpile and each treatment was repeated by five times. The experiment was following complete randomize design procedure. After sixteen days of research, the soil sample from each pot was analyzed for soil FDA activity, number of flagellate and nematodes. Furthermore, one kg of the soil from each pot was taken and every pot was grown by Paraserianthes falcataria seedling with the age of five days and continued its growth for two months. The results indicated that the soil FDA activity, number of flagellate and nematodes among treatments were significantly differences. In addition, it indicated the significant differences in dry weight of shoot, root, total plant, and root to shoot ratio of P. falcataria seedlings. It concluded that the combination of an individual number of epigeic and endogeic earthworms improved soil biological quality of stock pile, amd Â most suitable for seedlings growth in nickel mining area.